МОЛОЧНАЯ ПРОДУКТИВНОСТЬ ЛОШАДЕЙ КАЗАХСКОЙ, НОВОАЛТАЙСКОЙ ПОРОД И ИХ ПОМЕСЕЙ - Асанбаев, Т.Ш. (Mongolian Journal of Agricultural Sciences, 2014)
Abstract: Novoaltayskaya breed combined together with local Altay horses with such breeds as Soviet, Russian, and Lithuanian carthorses are definitely improving Kazakh horses according to meat and milk productivity as well. Mixed Novoaltaysko-kazakh mare by yearly and annual feeding produced more milk and demonstrated high milk index in comparison to existing matrix in Pavlodar Priirtyshya steppes. Hybrids overcome previous Kazakh breed on milk productivity in 726 liters, novoaltayskaya in 186 liters, in milk index accordingly in 75,5 and 73,0. РЕЗЮМЕ: Новоалтайская порода выведенная путем скрещивания местных алтайских лошадей с такими породами как советская, русская и литовская тяжеловозные породы, несомненно является улучшателем казахской породы лошадей как мясной так и по молочной продуктивности. Помесные новоалтайско-казахские кобылы при круглогодовом пастбищно-тебеневочном содержании проявили более высокую молочную продуктивность и индекс молочности, нежели исходные маточные породы в условиях степной зоны Павлодарского Прииртышья. Помеси превосходят исходную казахскую породу по молочности на 726 л, новоалтайскую на 186 л, по индексу молочности соответственно на 75,5 и 73,0. DOI: http://dx.doi.org/10.5564/mjas.v10i1.296